IDENTIFYING ENGLISH – INDONESIAN SUBTITLES TRANSLATION TECHNIQUES OF SUBTITLES IN “INCREDIBLES 2” MOVIE - Najiha, Siti; Dahnilsyah, Dahnilsyah; M. Syarfi, M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The objective of this research is to identify the frequent translation techniques used by the translator in "Incredibles 2" movie. This research was a content analysis method as the research design. The data used in this research are the hard file subtitles from the "Incredibles 2" movie in both English and Indonesian subtitles. The researcher identifies half of the subtitles movie and uses translation techniques from Molina and Albir (2002). The researcher used four translation techniques from Molina and Albir (2002) for identifying the subtitles. They are amplification technique, borrowing technique, literal translation technique, and reduction technique. The data obtained by identified the subtitle, classified each data according to the translation technique, and calculated the percentage. The researcher found 459 data from 1147 data. The result shows that the frequent translation technique is literal translation technique with 181 data represent 39.43%. The other three translation techniques are amplification techniques with 45 data represents 9.80%, borrowing techniques with 107 data represents 23.31%, and reduction technique with 126 data represents 27.45%.Key Words: Translation Techniques, Subtitles, Content Analysis, Movie